2021
DOI: 10.1038/s41598-021-89204-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination and dietary risk assessment of 284 pesticide residues in local fruit cultivars in Shanghai, China

Abstract: The presence of pesticide residues has become one of the main risk factors affecting the safety and quality of agro-food. In this study, a multi-residue method for the analysis of 284 pesticides in five local fruit cultivars in Shanghai was developed based on ultrahigh-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-QTOF/MS). The limits of determination and the limits of quantitation of pesticides were 0.6–10 and 2–30 μg/kg, respectively. A total of 44, 10, 10, 18, and 7 pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 40 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…In this study, collectively, there were 769 verifiable nutrition claims made by the 207 milk products targeting COA, and only three claims (i.e., one “reduced fat” and two “contains dietary fibre”) from three products failed to comply with GB 28050-2011. Previously, Zhang reported 5.0% of fruit products available in Shanghai did not comply with the maximum residual limits for pesticides in food (GB 2763-2019) [ 69 ]. Wang summarised 540 pork hazard incidents based on 23,515 pork inspection cases from 2014 to 2016 (averaged at 2.3%), violating the hygienic standard for fresh (frozen) meat (GB 2707-2005), maximum levels of contaminants in foods (GB 2762-2012), general rules on pre-packaged food labelling (GB 7718-2011), etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, collectively, there were 769 verifiable nutrition claims made by the 207 milk products targeting COA, and only three claims (i.e., one “reduced fat” and two “contains dietary fibre”) from three products failed to comply with GB 28050-2011. Previously, Zhang reported 5.0% of fruit products available in Shanghai did not comply with the maximum residual limits for pesticides in food (GB 2763-2019) [ 69 ]. Wang summarised 540 pork hazard incidents based on 23,515 pork inspection cases from 2014 to 2016 (averaged at 2.3%), violating the hygienic standard for fresh (frozen) meat (GB 2707-2005), maximum levels of contaminants in foods (GB 2762-2012), general rules on pre-packaged food labelling (GB 7718-2011), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst examining compliance of nutritional claims with local regulations seems to be the common situation in similar research [ 69 , 70 ], this study went above and beyond mere compliance with government regulations to examine meaningfulness of the claims when compared to other products in the same category. The results indeed suggested that GB 28050-2011, for instance by being set too low, failed to differentiate between milks with various claims on multiple occasions.…”
Section: Discussionmentioning
confidence: 99%
“…The chronic dietary intake risk of each pesticide was determined using the national estimated daily intake (NEDI) and acceptable daily intake (ADI) [ 24 , 25 ]. The daily dietary exposure of a pesticide was calculated based on the following equation: where NEDI is the national estimated daily intake (mg/kg·d); STMR is the median residue, taking the average residual value (mg/kg); F is the average daily consumption of coix seed (kg/d)—31.1 g of coix seed per adult per day according to the survey; bw is average weight for adults (estimated to be approximately 60 kg).…”
Section: Methodsmentioning
confidence: 99%
“…The residue values ranged from 0.01 to 0.28 mg/kg, which was lower than the maximum residual level (MRL) value of European Union (0.3 mg/kg). In another study of five local fruit cultivars in Shanghai, 1 out of 40 peach samples was positive for pyridaben, with a residue value of 7.8 μg/kg ( Zhang et al, 2021 ). Pesticide residues in 2922 mandarin, tangerine, and orange samples from China were evaluated during the period of 2013–2018 ( Li et al, 2020 ).…”
Section: Occurrence Of Pyridabenmentioning
confidence: 99%